Relationship Between Socioeconomic Status and Win-Win Values: Mediating Roles of Childhood Neglect and Self-Continuity - Zhang, Feng; Zhang, Shan; Gao, Xu (Frontiers in Psychiatry, 2022)
The family plays a key role on the development of children. One with low socioeconomic status was more likely to suffer childhood neglect, which might not only impacted on self-continuity but development of win-win values. Using cross-sectional data from 489 participants, this study conducted a mediation model to examine the roles of childhood neglect and self-continuity between socioeconomic status and win-win values. Our results showed that childhood neglect and self-continuity fully mediated the effect of socioeconomic status on win-win values. Specifically, socioeconomic status might affect win-win values through three roles: the individual mediating role of childhood neglect, the individual mediating role of self-continuity, and the multiple mediation roles of childhood neglect and self-continuity.